Não foi por amor: o jornalismo multiplataforma e investigativo do projeto #UmaPorUma sobre as mulheres assassinadas em Pernambuco - Andrade, Lorena Borges de (2019)
The purpose of this research is to investigate how the strategy of multiplataform #UmaPorUma, a project from Sistema Jornal do Commercio de Comunicação (SJCC) that maps the murdered women in the State of Pernambuco throughout 2018 - and tells their story, can help to bring more visibility to the murdered women in the State. The hypothesis is that the project helps to fight the disinformation around gender-based violence and the impunity of those cases. To accomplish the proposed goal, a systematic observation from all the published data in the platforms that compose #UmaPorUma - website, tv, radio and publishings - has been done, we built observation sheets and also semi-structured interviews with the professionals that took part of the project. The results point to the confirmation of our hypothesis and show that the multiplatform distribution was crucial not only for #UmaPorUma to bring visibility to the murders, but also to put gender-based violence widely into debate.